Solar power support of luxury boat - Wawrzyniak, Aleksandra (Neutro à Terra, 2021)
This document contains project of solar power sup-port for luxury boat. This project is design of electrical installation of the boat with solar panel system as an additional energy source what in case of an emergency it is possible to supply loads necessary for communication and safety. Electric propulsion system allows better maneuvering at low speed. This work presents design of electrical installation of the base and of the solar part of the system with all the necessary elements. Simulation of solar design and power analysis of solar part of the system are presented, what provides with good picture of its influence on the system. Obtained results are promising and can potentially be extended to bigger systems. This kind of solution highly increases reliability of the system.